2013
DOI: 10.1021/om4000709
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Ethylene with 1-Hexene and 1-Octene Catalyzed by Fluorenyl N-Heterocyclic Carbene Ligated Rare-Earth Metal Precursors

Abstract: Rare-earth metal bis(alkyl) complexes (Flu–NHC)Ln(CH2SiMe3)2 (Ln = Dy (1), Er (2), Sc (3)) attached by fluorenyl-modified N-heterocyclic carbene ligands ((Flu H–NHC–H)Br) have been synthesized by treatment of (FluH–NHC–H)Br with (trimethylsilylmethyl)lithium (LiCH2SiMe3) and rare-earth metal tris(alkyl)s (Ln(CH2SiMe3)3(THF)2) via double-deprotonation reactions in moderate to high yields. Under mild conditions (40 °C and normal ethylene pressure), the scandium precursor 3, upon activation of Al i Bu3 and [Ph3C]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…Thus the isolated P(E-co-Oct) polymers varied from opaque crystalline solids with high melting points, e.g., T m = 103.6 • C, to transparent elastomers. This represents the first rare-earth metal based homogeneous catalyst that can initiate the copolymerization of ethylene and 1-octene, the catalytic performances of which are comparable with those reported for the most active group 4 metallocene systems [120]. Some of the amidino-boratabenzene complexes shown in Scheme 105 have been found to exhibit excellent catalytic activity for ethylene polymerization upon activation [80].…”
Section: Heterobimetallic Organolanthanide Complexessupporting
confidence: 67%
See 1 more Smart Citation
“…Thus the isolated P(E-co-Oct) polymers varied from opaque crystalline solids with high melting points, e.g., T m = 103.6 • C, to transparent elastomers. This represents the first rare-earth metal based homogeneous catalyst that can initiate the copolymerization of ethylene and 1-octene, the catalytic performances of which are comparable with those reported for the most active group 4 metallocene systems [120]. Some of the amidino-boratabenzene complexes shown in Scheme 105 have been found to exhibit excellent catalytic activity for ethylene polymerization upon activation [80].…”
Section: Heterobimetallic Organolanthanide Complexessupporting
confidence: 67%
“…The catalysts (Flu-NHC)Ln(CH 2 SiMe 3 ) 2 (Ln = Sc, Dy, Er) containing fluorenylmodified N-heterocyclic carbene ligands (Flu-NHC) have been synthesized by treatment of (FluH-NHC-H)Br with (trimethylsilylmethyl)lithium (LiCH 2 SiMe 3 ) and rare-earth metal tris(alkyl)s (Ln(CH 2 SiMe 3 ) 3 (THF) 2 ) via double deprotonation reactions in moderate to high yields (Scheme 143) [120].…”
Section: Heterobimetallic Organolanthanide Complexesmentioning
confidence: 99%
“…The C NMR spectrum (Fig. ) revealed copolymer resonances at 14.0, 22.9, 30.0, 30.5, 32.2, 34.6 and 38.2 ppm, which can be assigned to the carbon atoms in CH 3 , CH 2 (2), CH 2 (β, 5), CH 2 (δ, ϵ, 4), CH 2 (γ), CH 2 (3), CH 2 (α) and CH . This indicated that no contiguous 1‐octene units were formed and only the signals from the joint EOE, EEO, OEO and EEE units were present.…”
Section: Resultsmentioning
confidence: 98%
“…The results indicated that, compared with ethylene homopolymerization, the use of a comonomer in the polymerization feed decreased the catalyst activity (110.7 kg mol V −1 (0.5 h) −1 ) and changed the properties of the polymer product; first it lowered its molar mass ( M w = 160 × 10 3 g mol −1 , M w / M n = 1.9). Therefore, the comonomer can accelerate the β‐hydrogen elimination reaction in the process as well as direct the chain‐transfer reaction towards a higher 1‐olefin . The content of incorporated comonomer, as determined by NMR, reached 2.2 mol%.…”
Section: Resultsmentioning
confidence: 98%
“…A series of CCC-pincer 2,6-xylenyl bis(carbene)-ligated Ln dibromides (60)(61)(62)(63)(64)(65)(66)(67)(68)(69) were synthesized via the treatment of imidazolium dibromide proligands and LnCl 3 with dropwise addition of n BuLi (Figure 15) [79,80]. The Y, Nd, Gd, Dy, and Ho complexes exhibited high activity and cis-1,4 selectivity (99.6%, 25 • C) in the polymerization of isoprene under activation with AlR 3 (R = Me, Et, i Bu) and [Ph 3 C][B(C 6 F 5 ) 4 ], while the others were inactive.…”
Section: Rare Earth Catalysts Containing a Tridentate Nhc Ligandmentioning
confidence: 99%